(211) oriented ZnTe growth on m‐plane sapphire by MBE. Issue 11 (7th October 2013) - Nakasu, Taizo; Kobayashi, Masakazu; Togo, Hiroyoshi; Asahi, Toshiaki; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract Single‐crystalline and single domain ZnTe thin films are sought for high‐performance terahertz wave detectors, and ZnTe/sapphire heterostructures were considered since the Electro‐Optical (EO) effect could be obtained only from epilayers. ZnTe epilayers were grown on m‐plane sapphire substrates by molecular beam epitaxy, and the potential of single domain epilayers was explored. Through the X‐ray diffraction pole figure measurement it was confirmed that one (100) oriented ZnTe domain along with two kinds of (211) oriented domains were formed on the m‐plane sapphire when the layer was grown at 340 °C. When the layer was grown at 350 °C, the (211) oriented domain dominated the film. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)